Principles and practice of nursing - Henderson, Virginia (Macmillan, 1978)
xiii, 2119 p. : 26 cm; Editions for 1922-1955 by B. Harmer published under title: Textbook of the principles and practice of nursing; 4th ed. (1939) by B. Harmer and V. Henderson and 5th ed. (1955) rev. by V. Henderson; Includes bibliographies and index
Keywords: Nursing